Enhanced sludge electrokinetic dewatering using pre-treatment techniques - Tien, Matthew Wei Xian (2014)
Electrokinetic process has increasingly being recognised globally as an efficient and low cost alternative to sludge dewatering. It is a process of applying electric field to increase liquid/solids separation and hence enhance dewatering efficiency. Although numerous studies have validated the use of sludge pre-treatment techniques to enhance electrokinetic dewatering, the effects of pre-treatment on the sludge physico-chemical properties and its dewatering capability were not well discussed. Limited researches have also being done to explore the sludge energy content and combustion behaviour after electrokinetic process. In this study, the effects of Freeze Thaw, Ultrasound and pH adjustment as pre-treatment techniques on the dewatering capability and physico-chemical properties of sludge were explored. In addition, the effects of the pre-treatment techniques on the sludge organic matter, energy content and the combustion behaviour at different segment of the final sludge cake were investigated.